Green coconut (Cocos nucifera L.) waste management for a food processing company - Juárez-Piedra, Verónica Fiorella (2025)
Costa Rica harvests 15 000 annual tons of coconut, that can be consumed in an early or green development stage, which is denominated in various Latin American countries as “pipa”. Its inadequate disposal can have negative environmental impacts like landscape changes, insect proliferation and rodents. This paper presents a literature review focused on the application of green coconut as an agricultural substrate, an analysis of basic physical and chemical properties, and strategies for its management and valorization. It was found that the applications for green coconut are varied and that the main use for the waste in Costa Rica is in agriculture, having the opportunity of being used as fibers and dust or peat, as well as part of a compost matrix. 392 units of whole coconut can be stored per m3 , while 832 units/m3 can be stored crushed. Green coconut has a high electrical conductivity (1389 µS/cm), which is why washing and/or pressing of the fruits is necessary. To obtain dust and fibers, machinery like crushers and mills, space for drying and maturation, and a centrifuge or washing area; are required.